A method for preparing CDs composite Mo-La ion co-doped TiO2 nanotube array

Through CDS composite MO-LA ions doped method, the problem of non-bandwidth width and low optical quantum efficiency of pure TIO2 nanotubes in the field of photocatalytic is solved, and the effect of improving TIO2 optical quantum efficiency and broadening the range of optical response.

CN117839679BActive Publication Date: 2025-01-24KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410016335.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-05
Publication Date
2025-01-24
Estimated Expiration
2044-01-05

AI Technical Summary

Technical Problem

Pure TiO2 nanotubes have several key problems in the field of photocatalysis: their wide bandwidth is, resulting in a low response rate to ultraviolet light; the recombination rate of photogenerated electrons and holes is fast, resulting in low photo-quantum efficiency.

Method used

The preparation method of CDs (carbon dots) composite Mo-La ion co-doped TiO2 nanotube array is used to realize the co-doping of Mo6+ and La3+ through electrochemical method, and then the CDs and Mo-La-TiO2 nanotube are composited through electrophoresis method. .

Benefits of technology

Effectively improve the optical quantum efficiency of TIO2, broaden the range of light response, and improve the utilization rate of visible light, thereby improving the optical activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117839679B_ABST
    Figure CN117839679B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a CDs composite Mo-La ion co-doped TiO2 nanotube array, which belongs to the field of photocatalysis technology. The specific preparation method is: firstly, a titanium sheet is polished, cleaned and dried, and then an electric current is applied in an ammonium fluoride-ethylene glycol-water electrolyte solution to obtain a layer of TiO2 nanotube array film; then, the titanium sheet with the TiO2 nanotubes attached is placed in a molybdenum soluble inorganic salt solution and a lanthanum soluble inorganic salt solution, respectively, and Mo is obtained by electrochemical reaction. 6+ ‑La 3+ Co-doped TiO2 nanotubes; CDs were prepared by hydrothermal method, a CDs solution of a certain concentration was prepared, and Mo 6+ ‑La 3+ Co-doped TiO2 nanotubes were composited in CDs solution by electrophoresis to obtain CDs composite Mo 6+ ‑La 3+ Co-doped TiO2 nanotubes. The CDs composite Mo-La ion co-doped TiO2 nanotube array prepared by the present invention is attached to a titanium substrate in a thin film structure with a thickness of 1.5um to 3um and a tube diameter of 70nm to 100nm. The nanotubes are arranged in an orderly manner, with a flat surface, uniform tube diameter, and a circular shape.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a CDs composite Mo-La ion co-doped TiO2 nanotube array, belonging to the technical field of photocatalysts. Background Art

[0002] With the rapid development of human economy and society, the ecological environment pollution problems caused by it are becoming increasingly serious and affecting people's daily life and health. Using the photocatalytic properties of semiconductor materials to remove various pollutants in the environment is an effective method and has attracted widespread attention from the world. Nano-TiO2 semiconductor photocatalytic materials have become a research hotspot due to their outstanding properties such as high catalytic activity, good stability, low price, non-toxicity, and wide application range. However, at present, powdered nano-TiO2 particles are easy to agglomerate, difficult to recycle and reuse, and easily cause secondary pollution to the environment, which limits their practical application in the field of photocatalysis. Titanium dioxide nanotube arrays grown on titanium substrates can not only immobilize photocatalysts and solve the problem of difficult catalyst separation and recovery, but also overcome the shortcomings of poor stability and easy poisoning of suspended phase catalysts. At the same time, their special tubular structure has a larger specific surface area and adsorption capacity, which can provide higher reaction for photocatalytic degradation, and thus has received special attention. However, there are still two key problems with pure TiO2 nanotube arrays: first, its bandgap is wide (about 3.2eV for anatase type), which can only respond to ultraviolet light, and the utilization rate of sunlight is low; second, the recombination rate of photogenerated electrons and holes in pure TiO2 is very fast, generally occurring in the time scale range of picoseconds and nanoseconds, and the photon efficiency is very low. Researchers use methods such as doping, precious metal deposition, and semiconductor composite to modify it, and are committed to changing its bandgap and inhibiting the recombination of photogenerated electrons and holes. However, due to the many factors that affect the photocatalytic performance of titanium dioxide and their interactions, and each method has certain disadvantages, such as the high manufacturing cost of precious metal deposited TiO2 and the difficulty in controlling process parameters; the low stability of metal ion modified TiO2, and some metal ions are easy to become carrier recombination centers; the holes of non-metal doped TiO2 under visible light excitation have lower oxidation ability than those under ultraviolet light excitation, which makes it difficult to achieve the degradation of most organic matter under visible light, affecting its large-scale application in the industrial field. Therefore, more in-depth research and new exploration of titanium dioxide photocatalysts are needed. Summary of the invention

[0003] In order to solve the problems existing in the existing TiO2 nanotubes, the present invention provides a method for preparing a CDs (carbon dots) composite Mo-La ion co-doped TiO2 nanotube array. The CDs-Mo-La-TiO2 nanotube array prepared by the present invention is arranged regularly and orderly, has a flat surface, a tube diameter of about 70nm to 100nm, and a thickness of 1.5um to 3um. The specific preparation steps are as follows:

[0004] (1) Use pure titanium sheet as the substrate, polish until there are no obvious scratches on the surface, clean it, dry it and set it aside.

[0005] (2) dissolving ammonium fluoride in deionized water, adding ethylene glycol, and stirring evenly to obtain an ammonium fluoride-ethylene glycol-water solution as an electrolyte solution, using the titanium sheet treated in step (1) as an anode and the graphite sheet as a cathode, connecting a DC constant voltage power supply to the obtained electrolyte, controlling the oxidation voltage and time to perform anodization, and finally obtaining a titanium sheet with TiO2 nanotubes attached thereto, which is then cleaned and dried for later use.

[0006] (3) dissolving a soluble Mo inorganic salt in deionized water to prepare an electrolyte solution containing Mo ions, using the titanium sheet with attached titanium dioxide nanotubes obtained in step (2) as a cathode and a graphite sheet as an anode, applying a DC power supply, controlling the reaction voltage and reaction time, and carrying out Mo reaction. 6+ After the doping reaction is completed, a titanium sheet doped with Mo ions and TiO2 nanotubes is obtained, which is then cleaned, dried, and set aside.

[0007] (4) dissolving a soluble La inorganic salt in deionized water to prepare an electrolyte solution containing Mo ions, using the titanium sheet doped with Mo ions obtained in step (3) as a cathode and a graphite sheet as an anode, applying a DC power supply, and controlling the reaction voltage and reaction time to carry out La 3+ Doping reaction, after the reaction is completed, Mo-La co-doped TiO2 nanotube titanium sheet is obtained, which is cleaned, dried and set aside.

[0008] (5) The titanium sheet of Mo-La co-doped titanium dioxide nanotubes obtained in step (4) is placed in a muffle furnace for calcination to obtain a Mo-La ion co-doped TiO2 nanotube array.

[0009] (6) Glucose is dispersed in deionized water to form a glucose aqueous solution, which is added to a reactor for hydrolysis reaction to obtain a hydrolysis mixture, the mixture is centrifuged in a centrifuge to separate the suspension and the hydrochar, the hydrochar is washed, and then dried in an oven to obtain biochar, the biochar is dispersed in a NaOH solution, a H2O2 solution is added and stirred to obtain a golden transparent liquid, the pH value of the golden transparent liquid is adjusted, and then the liquid is dialyzed to obtain CDs (carbon dots).

[0010] (7) The CDs obtained in step (6) is dissolved in deionized water to prepare a CDs solution, the pH value of the CDs solution is adjusted, and the Mo-La-TiO2 nanotube array titanium sheet obtained in step (5) is used as a cathode and the graphite sheet is used as an anode. Electrophoresis is performed in the CDs solution to obtain CDs composite Mo-La-TiO2 nanotubes, which are then ultrasonically cleaned and dried.

[0011] Preferably, the specification of the pure titanium sheet in step (1) is 0.2 mm × 20 mm × 30 mm; it is polished with 200#, 400#, 800#, 1000#, 1500#, 2000#, and 2500# sandpaper in sequence until there are no obvious scratches on the surface; and ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water for 10 minutes each.

[0012] Preferably, in step (2), the volume ratio of deionized water to ethylene glycol is 95:5-80:20, and the concentration of ethylene glycol used is 95%; the amount of ammonium fluoride added to the deionized water is 0.1 mol / L-1 mol / L; the oxidation voltage is 10 V-40 V, and the oxidation time is 0.5 h-3 h.

[0013] Preferably, the inorganic salt of Mo in step (3) comprises any one of analytically pure sodium molybdate, ammonium molybdate, and magnesium molybdate, the amount of the inorganic salt of Mo added is 0.01 mol / L to 0.1 mol / L, the reaction voltage is 4 V to 10 V, and the reaction time is 0.5 h to 2 h.

[0014] Preferably, the inorganic salt of La in step (4) comprises any one of analytically pure lanthanum nitrate, lanthanum chloride and lanthanum sulfate, the amount of the inorganic salt of La added is 0.005 mol / L to 0.05 mol / L, the reaction voltage is 4 V to 10 V, and the reaction time is 0.5 h to 2 h.

[0015] Preferably, the molar ratio of Mo ions and La ions co-doped in step (3) and step (4) is 2:1.

[0016] Preferably, the calcination conditions in step (5) are: calcination temperature is 450°C to 550°C, heating rate is 4°C / min to 10°C / min, and calcination time is 2h to 4h.

[0017] Preferably, the amount of glucose added in step (6) is 66.7-200 g / L, and the conditions of the hydrothermal reaction are: a heating rate of 4°C / min-10°C / min, and a reaction at 150°C-250°C for 5h-8h; a centrifugal rate of 7000r / min-10000r / min, and a time of 5-10min; and the hydrochar is washed three times with deionized water and ethanol respectively.

[0018] Preferably, in step (6), the volume ratio of NaOH solution to H2O2 solution is 10:1-10:3, wherein the concentration of NaOH solution used is 0.05 mol / L-1 mol / L, and the concentration of H2O2 solution used is 7.5%; the amount of biochar added to the mixture of NaOH solution and H2O2 solution is 0.01 g / L-0.02 g / L, the pH value of the golden transparent liquid is adjusted to 5-7 with HCl, and then the golden transparent liquid is dialyzed for 24h-36h, and deionized water is replaced every 5-8h, wherein the ratio of the initially added golden transparent liquid to deionized water is 1:(70-100), and the dialysis bag is MW3500.

[0019] Preferably, in step (7), the amount of CDs added is 0.01-0.5 mg / ml, and the pH value of the CDs solution is adjusted to 8-10 with ammonia water; the electrophoresis voltage is 4V-10V, and the electrophoresis time is 4min-15min.

[0020] Principle of the invention: CDs (Carbon Dots) is a new type of carbon nanomaterial. The combination of CDs and TiO2 can effectively transfer electrons and prolong the survival time of electron-hole pairs, thereby effectively improving the photonic quantum efficiency of TiO2. At the same time, it can broaden the light response range of TiO2 and make the absorption spectrum of TiO2 red-shift, thereby improving the utilization rate of visible light. Transition metal Mo 6+ Radius (0.064nm) and Ti 4+ The ionic radius of TiO2 is similar to that of TiO2 (0.068nm), so it is easy to enter the lattice and replace Ti when doped with TiO2. 4+ , forming substitutional doping, so it is evenly distributed in TiO2, which is beneficial to the improvement of photocatalytic activity; at the same time, Mo 6+ As a high-valence ion, doping TiO2 will introduce free electrons to form donor energy levels, which can inhibit the recombination of photogenerated electrons and holes and reduce the threshold of TiO2 light absorption. 3+ The radius (0.115nm) is much larger than Ti 4+ The radius, La 3+ When doped with TiO2, it does not replace Ti 4+ Instead, La diffuses into the lattice to cause lattice distortion, making it easy for oxygen atoms on the surface of the TiO2 lattice to escape from the lattice and generate oxygen vacancies. 3+ As low-valent ions, doping TiO2 will introduce holes, form acceptor energy levels, reduce the band gap width, and improve photocatalytic activity. 6+ ,La 3+ The co-doping was combined by first achieving Mo by a two-step electrochemical method. 6+ ,La 3+Co-doping is used to complement each other's advantages, and then CDs and Mo are electrophoretically 6+ ,La 3+ Co-doped TiO2 composites achieve a superposition of advantages and effectively solve the problems existing in TiO2 itself through their synergistic effects.

[0021] Beneficial effects of the present invention

[0022] (1) The diameter, length, surface flatness and order of TiO2 nanotubes can be adjusted by adjusting the concentration of ammonium fluoride solution, the voltage of anodization and the reaction time.

[0023] (2) Mo and La ion co-doping is effectively achieved by adjusting the Mo and La ion concentrations, reaction voltage, and reaction time in secondary electrochemistry.

[0024] (3) Spherical CDs with a size less than 50 nm were obtained by controlling the hydrolysis reaction temperature, NaOH solution concentration, and H2O2 solution addition amount.

[0025] (4) By changing the amount of Mo and La ion doping and the concentration of CDs solution, the light absorption band edge and band gap width of titanium dioxide nanotubes can be adjusted to obtain a composite titanium dioxide photocatalytic material with high photocatalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the morphology of the homemade CDs.

[0027] Figure 2 Surface SEM morphologies of titanium dioxide nanotubes of Examples 1 to 4, wherein 1, 2, 3, and 4 correspond to Example 1, Example 2, Example 3, and Example 4, respectively.

[0028] Figure 3 The scanning electron microscope images of the cross-section of titanium dioxide nanotubes of Examples 1 to 4 are

[0029] Figure 4 These are UV-Vis test diagrams of Examples 1 to 4 and Comparative Examples 1 to 2.

[0030] Figure 5 Surface SEM morphologies of titanium dioxide nanotubes of Examples 5 to 8, wherein a, b, c, and d correspond to Example 5, Example 6, Example 7, and Example 8, respectively. DETAILED DESCRIPTION

[0031] Example 1

[0032] A thin film structure of CDs composite Mo-La ion co-doped TiO2 nanotubes, the specific preparation method is as follows:

[0033] (1) A 0.2 mm × 20 mm × 30 mm high-purity titanium sheet was used as the substrate and polished with 200#, 400#, 800#, 1000#, 1500#, 2000#, and 2500# sandpapers in sequence until there were no obvious scratches on the surface; then, ultrasonic cleaning was performed with acetone, anhydrous ethanol, and deionized water for 10 min each, and the sheet was dried for later use.

[0034] (2) Dissolve ammonium fluoride in deionized water in a beaker, and then add ethylene glycol with a concentration of 95% to prepare an ammonium fluoride electrolyte, wherein the volume ratio of deionized water to ethylene glycol is 95:5, and the amount of ammonium fluoride added is 0.25 mol / L. Stir it evenly on a magnetic stirrer. The titanium sheet treated in (1) is used as the anode and the graphite sheet is used as the cathode. Connect a DC constant voltage power supply to the obtained electrolyte, adjust the voltage to 30 V, and determine the oxidation time to be 1 hour. After the oxidation is completed, the prepared TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute, and then dried for use.

[0035] (3) Sodium molybdate is used as a Mo ion source, and sodium molybdate is dissolved in deionized water to obtain a sodium molybdate aqueous solution as an electrolyte, wherein the amount of sodium molybdate added is 0.01 mol / L. The titanium sheet with TiO2 nanotubes attached obtained in step (2) is used as a cathode, and the graphite sheet is used as an anode. A DC power supply is applied, and the voltage is adjusted to 6 V. The oxidation time is 1 hour. After the end, the TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute, and then dried for use.

[0036] (4) Lanthanum nitrate is used as a La ion source, and lanthanum nitrate is dissolved in deionized water to obtain a lanthanum nitrate aqueous solution as an electrolyte, wherein the amount of lanthanum nitrate added is 0.005 mol / L, and the Mo-doped TiO2 nanotubes dried and set aside in step (3) are placed at the cathode, and graphite is placed at the anode, and an electrochemical reaction is performed to dope La ions, and the voltage is adjusted to 6 V and the oxidation time is 1 hour. After the end, the Mo and La co-doped TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute and dried for later use.

[0037] (5) The Mo and La co-doped TiO2 nanotubes obtained in step (4) are placed in a muffle furnace for calcination, the heating rate is controlled to be 5°C / min, the calcination temperature is 450°C, the calcination time is 3h, and the Mo and La ion co-doped TiO2 nanotube arrays are obtained after cooling in the furnace.

[0038] (6) Dispersing glucose in deionized water, wherein the amount of glucose added is 0.1 g / ml, adding the obtained glucose aqueous solution into a reactor, controlling the heating rate of the reactor to 5°C / min, performing a hydrolysis reaction at 180°C, and obtaining a hydrolysis mixture for 6 hours; placing the mixture in a centrifuge and centrifuging it at 7000 r / min for 7 minutes to separate the suspension and the hydrochar, washing the hydrochar with deionized water and ethanol for 3 times respectively, and then drying it in an oven to obtain biochar; dispersing the biochar in 0.4 mol / L NaOH solution was added with H2O2 solution and stirred at room temperature for 8 h to obtain a golden transparent liquid, wherein the volume ratio of 0.4 mol / L NaOH solution to H2O2 solution was 10:2, the amount of biochar added was 0.02 g / L, the pH value of the golden transparent liquid was adjusted to 7 with HCl, and then the liquid was dialyzed for 24 h, wherein deionized water was replaced every 6 h, the volume ratio of the initially added golden transparent liquid to deionized water was 1:100, the dialysis bag was MW3500, and CDs were obtained after removing the salt.

[0039] (7) The CDs obtained in step (6) is dissolved in deionized water at a dosage of 0.05 mg / ml, and the pH value of the CDs solution is adjusted to 9 with aqueous ammonia. The Mo-La-TiO2 nanotube array titanium sheet obtained in step (5) is used as the cathode and the graphite sheet is used as the anode. Electrophoresis is performed in the CDs solution at a voltage of 6 V for 6 min. After the electrophoresis, the CDs-composite Mo-La-TiO2 nanotubes are ultrasonically cleaned for 30 s and dried in an electric blower drying oven to obtain CDs-composite Mo-La-TiO2 nanotubes.

[0040] Example 2

[0041] A thin film structure of CDs composite Mo-La ion co-doped TiO2 nanotubes, the specific preparation method is as follows:

[0042] (1) A 0.2 mm × 20 mm × 30 mm high-purity titanium sheet was used as the substrate and polished with 200#, 400#, 800#, 1000#, 1500#, 2000#, and 2500# sandpapers in sequence until there were no obvious scratches on the surface; then, ultrasonic cleaning was performed with acetone, anhydrous ethanol, and deionized water for 10 min each, and the sheet was dried for later use.

[0043] (2) Dissolve ammonium fluoride in deionized water in a beaker, and then add ethylene glycol to prepare an ammonium fluoride electrolyte, wherein the volume ratio of deionized water to ethylene glycol is 80:20, and the amount of ammonium fluoride added is 0.1 mol / L. Stir it evenly on a magnetic stirrer. The titanium sheet treated in (1) is used as the anode and the graphite sheet is used as the cathode. Connect a DC constant voltage power supply to the obtained electrolyte, adjust the voltage to 10 V, and determine the oxidation time to be 3 h. After the oxidation is completed, the prepared TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 min, and then dried for use.

[0044] (3) Using ammonium molybdate as the Mo ion source, dissolving ammonium molybdate in deionized water to obtain an ammonium molybdate aqueous solution as the electrolyte, wherein the amount of ammonium molybdate added is 0.1 mol / L, using the titanium sheet with TiO2 nanotubes attached obtained in step (2) as the cathode, and the graphite sheet as the anode, applying a DC power supply, adjusting the voltage to 4 V, and the oxidation time to 2 h. After the oxidation, the TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 min, and then dried for use.

[0045] (4) Lanthanum chloride is used as a La ion source, and lanthanum chloride is dissolved in deionized water to obtain a lanthanum chloride aqueous solution as an electrolyte, wherein the amount of lanthanum chloride added is 0.05 mol / L, and the Mo-doped TiO2 nanotubes dried and set aside in step (3) are placed at the cathode, and graphite is placed at the anode, and an electrochemical reaction is performed to dope La ions, and the voltage is adjusted to 10 V and the oxidation time is 0.5 h. After the end, the Mo and La co-doped TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 min and dried for later use.

[0046] (5) The Mo and La co-doped TiO2 nanotubes obtained in step (4) are placed in a muffle furnace for calcination, the heating rate is controlled to be 4°C / min, the calcination temperature is 450°C, the calcination time is 4h, and the Mo and La ion co-doped TiO2 nanotube arrays are obtained after cooling in the furnace.

[0047] (6) Dispersing glucose in deionized water, wherein the amount of glucose added is 0.067 g / ml, adding the obtained glucose aqueous solution into a reactor, controlling the heating rate of the reactor to be 4°C / min, performing a hydrolysis reaction at 150°C, and obtaining a hydrolysis mixture for 6 hours; placing the mixture in a centrifuge and centrifuging at 8000 r / min for 5 minutes to separate the suspension and the hydrochar, washing the hydrochar with deionized water and ethanol for 3 times respectively, and then drying it in an oven to obtain biochar; dispersing the biochar in 0.05 mol / L N A 7.5% H2O2 solution was added to the aOH solution and stirred at room temperature for 8 hours to obtain a golden transparent liquid, wherein the volume ratio of 0.4 mol / L NaOH solution to H2O2 solution was 10:1, the amount of biochar added was 0.015 g / L, the pH value of the golden transparent liquid was adjusted to 5 with HCl, and then the liquid was dialyzed for 36 hours, wherein deionized water was replaced every 5 hours, the volume ratio of the initially added golden transparent liquid to deionized water was 1:80, the dialysis bag was MW3500, and CDs were obtained after removing the salt.

[0048] (7) The CDs obtained in step (6) is dissolved in deionized water at a dosage of 0.01 mg / ml. The pH value of the CDs solution is adjusted to 8 with aqueous ammonia. The Mo-La-TiO2 nanotube array titanium sheet obtained in step (5) is used as a cathode and the graphite sheet is used as an anode. Electrophoresis is performed in the CDs solution at a voltage of 4 V for 12 min. After the electrophoresis, the CDs-composite Mo-La-TiO2 nanotubes are ultrasonically cleaned for 30 s and dried in an electric blower drying oven to obtain CDs-composite Mo-La-TiO2 nanotubes.

[0049] Example 3

[0050] A thin film structure of CDs composite Mo-La ion co-doped TiO2 nanotubes, the specific preparation method is as follows:

[0051] (1) A 0.2 mm × 20 mm × 30 mm high-purity titanium sheet was used as the substrate and polished with 200#, 400#, 800#, 1000#, 1500#, 2000#, and 2500# sandpapers in sequence until there were no obvious scratches on the surface; then, ultrasonic cleaning was performed with acetone, anhydrous ethanol, and deionized water for 10 min each, and the sheet was dried for later use.

[0052] (2) Dissolve ammonium fluoride in deionized water in a beaker, and then add ethylene glycol with a concentration of 95% to prepare an ammonium fluoride electrolyte, wherein the volume ratio of deionized water to ethylene glycol is 95:5, and the amount of ammonium fluoride added is 1 mol / L. Stir it evenly on a magnetic stirrer. The titanium sheet treated in (1) is used as the anode and the graphite sheet is used as the cathode. Connect a DC constant voltage power supply to the obtained electrolyte, adjust the voltage to 40 V, and determine the oxidation time to be 0.5 h. After the oxidation is completed, the prepared TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 min, and then dried for use.

[0053] (3) Using magnesium molybdate as a Mo ion source, dissolving magnesium molybdate in deionized water to obtain a magnesium molybdate aqueous solution as an electrolyte, wherein the amount of magnesium molybdate added is 0.01 mol / L, using the titanium sheet with TiO2 nanotubes attached obtained in step (2) as a cathode, and the graphite sheet as an anode, applying a DC power supply, adjusting the voltage to 10 V, and the oxidation time to 0.5 h. After the oxidation, the TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 min, and then dried for use.

[0054] (4) Lanthanum sulfate is used as a La ion source, and lanthanum sulfate is dissolved in deionized water to obtain a lanthanum sulfate aqueous solution as an electrolyte, wherein the amount of lanthanum sulfate added is 0.005 mol / L, and the Mo-doped TiO2 nanotubes dried and set aside in step (3) are placed at the cathode, and graphite is placed at the anode, and an electrochemical reaction is performed to dope La ions, and the voltage is adjusted to 4 V and the oxidation time is 2 h. After the end, the Mo and La co-doped TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 min and dried for later use.

[0055] (5) The Mo and La co-doped TiO2 nanotubes obtained in step (4) are placed in a muffle furnace for calcination, the heating rate is controlled at 10°C / min, the calcination temperature is 550°C, the calcination time is 2h, and the Mo and La ion co-doped TiO2 nanotube arrays are obtained after cooling in the furnace.

[0056] (6) Dispersing glucose in deionized water, wherein the amount of glucose added is 0.2 g / ml, adding the obtained glucose aqueous solution into a reactor, controlling the heating rate of the reactor to be 10°C / min, performing a hydrolysis reaction at 250°C, and obtaining a hydrolysis mixture for 6 hours; placing the mixture in a centrifuge and centrifuging it at 10,000 r / min for 10 minutes to separate the suspension and the hydrochar, washing the hydrochar with deionized water and ethanol for 3 times respectively, and then drying it in an oven to obtain biochar; dispersing the biochar in 1 mol / L of NaOH solution, add H2O2 solution and stir at room temperature for 8h to obtain a golden transparent liquid, wherein the volume ratio of 0.4mol / L NaOH solution to H2O2 solution is 10:3, the amount of biochar added is 0.01g / L, the pH value of the golden transparent liquid is adjusted to 6 with HCl, and then the liquid is dialyzed for 32h, wherein deionized water is replaced every 8h, the volume ratio of the initially added golden transparent liquid to deionized water is 1:70, the dialysis bag is MW3500, and CDs are obtained after removing the salt.

[0057] (7) The CDs obtained in step (6) is dissolved in deionized water at a dosage of 0.5 mg / ml, and the pH value of the CDs solution is adjusted to 9 with aqueous ammonia. The Mo-La-TiO2 nanotube array titanium sheet obtained in step (5) is used as the cathode and the graphite sheet is used as the anode. Electrophoresis is performed in the CDs solution at a voltage of 10 V for 4 min. After the electrophoresis, the CDs-composite Mo-La-TiO2 nanotubes are ultrasonically cleaned for 30 s and dried in an electric blower drying oven to obtain CDs-composite Mo-La-TiO2 nanotubes.

[0058] Example 4

[0059] A thin film structure of CDs composite Mo-La ion co-doped TiO2 nanotubes, the specific preparation method is as follows:

[0060] (1) A 0.2 mm × 20 mm × 30 mm high-purity titanium sheet was used as the substrate and polished with 200#, 400#, 800#, 1000#, 1500#, 2000#, and 2500# sandpapers in sequence until there were no obvious scratches on the surface; then, ultrasonic cleaning was performed with acetone, anhydrous ethanol, and deionized water for 10 min each, and the sheet was dried for later use.

[0061] (2) Dissolve ammonium fluoride in deionized water in a beaker, and then add ethylene glycol with a concentration of 95% to prepare an ammonium fluoride electrolyte, wherein the volume ratio of deionized water to ethylene glycol is 95:5, and the amount of ammonium fluoride added is 0.25 mol / L. Stir it evenly on a magnetic stirrer. The titanium sheet treated in (1) is used as the anode and the graphite sheet is used as the cathode. Connect a DC constant voltage power supply to the obtained electrolyte, adjust the voltage to 30 V, and determine the oxidation time to be 1 hour. After the oxidation is completed, the prepared TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute, and then dried for use.

[0062] (3) Sodium molybdate is used as a Mo ion source, and sodium molybdate is dissolved in deionized water to obtain a sodium molybdate aqueous solution as an electrolyte, wherein the amount of sodium molybdate added is 0.02 mon / L. The titanium sheet with TiO2 nanotubes attached obtained in step (2) is used as a cathode, and the graphite sheet is used as an anode. A DC power supply is applied, and the voltage is adjusted to 6 V. The oxidation time is 1 hour. After the end, the TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute, and then dried for use.

[0063] (4) Lanthanum nitrate is used as a La ion source, and lanthanum nitrate is dissolved in deionized water to obtain a lanthanum nitrate aqueous solution as an electrolyte, wherein the amount of lanthanum nitrate added is 0.01 mol / L, and the Mo-doped TiO2 nanotubes dried and set aside in step (3) are placed at the cathode, and graphite is placed at the anode, and an electrochemical reaction is performed to dope La ions, and the voltage is adjusted to 6 V and the oxidation time is 1 hour. After the end, the Mo and La co-doped TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute and dried for later use.

[0064] (5) The Mo and La co-doped TiO2 nanotubes obtained in step (4) are placed in a muffle furnace for calcination, the heating rate is controlled to be 5°C / min, the calcination temperature is 450°C, the calcination time is 3h, and the Mo and La ion co-doped TiO2 nanotube arrays are obtained after cooling in the furnace.

[0065] (6) Dispersing glucose in deionized water, wherein the amount of glucose added is 0.1 g / ml, adding the obtained glucose aqueous solution into a reactor, controlling the heating rate of the reactor to 5°C / min, performing a hydrolysis reaction at 180°C, and obtaining a hydrolysis mixture for 6 hours; placing the mixture in a centrifuge and centrifuging it at 7000 r / min for 7 minutes to separate the suspension and the hydrochar, washing the hydrochar with deionized water and ethanol for 3 times respectively, and then drying it in an oven to obtain biochar; dispersing the biochar in 0.4 mol / L NaOH solution was added with H2O2 solution and stirred at room temperature for 8 h to obtain a golden transparent liquid, wherein the volume ratio of 0.4 mol / L NaOH solution to H2O2 solution was 10:2, the amount of biochar added was 0.02 g / L, the pH value of the golden transparent liquid was adjusted to 7 with HCl, and then the liquid was dialyzed for 24 h, wherein deionized water was replaced every 6 h, the volume ratio of the initially added golden transparent liquid to deionized water was 1:100, the dialysis bag was MW3500, and CDs were obtained after removing the salt.

[0066] (7) The CDs obtained in step (6) is dissolved in deionized water at a dosage of 0.05 mg / ml, and the pH value of the CDs solution is adjusted to 10 with aqueous ammonia. The Mo-La-TiO2 nanotube array titanium sheet obtained in step (5) is used as a cathode and the graphite sheet is used as an anode. Electrophoresis is performed in the CDs solution at a voltage of 6 V for 15 min. After the electrophoresis, the CDs-composite Mo-La-TiO2 nanotubes are ultrasonically cleaned for 30 s and dried in an electric blower drying oven to obtain CDs-composite Mo-La-TiO2 nanotubes.

[0067] Example 5

[0068] A thin film structure of CDs composite Mo-La ion co-doped TiO2 nanotubes, the specific preparation steps are as follows:

[0069] (1) A 0.2 mm × 20 mm × 30 mm high-purity titanium sheet was used as the substrate and polished with 200#, 400#, 800#, 1000#, 1500#, 2000#, and 2500# sandpapers in sequence until there were no obvious scratches on the surface; then, ultrasonic cleaning was performed with acetone, anhydrous ethanol, and deionized water for 10 min in sequence and dried for later use.

[0070] (2) Dissolve ammonium fluoride in deionized water in a beaker, and then add ethylene glycol with a concentration of 95% to prepare an ammonium fluoride electrolyte, wherein the volume ratio of deionized water to ethylene glycol is 95:5, and the amount of ammonium fluoride added is 0.25 mol / L. Stir it evenly on a magnetic stirrer. The titanium sheet treated in (1) is used as the anode and the graphite sheet is used as the cathode. Connect a DC constant voltage power supply to the obtained electrolyte, adjust the voltage to 10 V, and determine the oxidation time to be 1 hour. After the oxidation is completed, the prepared TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute, and then dried for use.

[0071] (3) Sodium molybdate is used as a Mo ion source, and sodium molybdate is dissolved in deionized water to obtain a sodium molybdate aqueous solution as an electrolyte, wherein the amount of sodium molybdate added is 0.01 mol / L. The titanium sheet with TiO2 nanotubes attached obtained in step (2) is used as a cathode, and the graphite sheet is used as an anode. A DC power supply is applied, and the voltage is adjusted to 6 V. The oxidation time is 1 hour. After the end, the TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute, and then dried for use.

[0072] (4) Lanthanum nitrate is used as a La ion source, and lanthanum nitrate is dissolved in deionized water to obtain a lanthanum nitrate aqueous solution as an electrolyte, wherein the amount of lanthanum nitrate added is 0.005 mol / L, and the Mo-doped TiO2 nanotubes dried and set aside in step (3) are placed at the cathode, and graphite is placed at the anode, and an electrochemical reaction is performed to dope La ions, and the voltage is adjusted to 6 V and the oxidation time is 1 hour. After the end, the Mo and La co-doped TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute and dried for later use.

[0073] (5) The Mo and La co-doped TiO2 nanotubes obtained in step (4) are placed in a muffle furnace for calcination, the heating rate is controlled to be 5°C / min, the calcination temperature is 450°C, the calcination time is 3h, and the Mo and La ion co-doped TiO2 nanotube arrays are obtained after cooling in the furnace.

[0074] (6) Dispersing glucose in deionized water, wherein the amount of glucose added is 0.1 g / ml, adding the obtained glucose aqueous solution into a reactor, controlling the heating rate of the reactor to 5°C / min, performing a hydrolysis reaction at 180°C, and obtaining a hydrolysis mixture for 6 hours; placing the mixture in a centrifuge and centrifuging it at 7000 r / min for 7 minutes to separate the suspension and the hydrochar, washing the hydrochar with deionized water and ethanol for 3 times respectively, and then drying it in an oven to obtain biochar; dispersing the biochar in 0.4 mol / L NaOH solution was added with H2O2 solution and stirred at room temperature for 8 h to obtain a golden transparent liquid, wherein the volume ratio of 0.4 mol / L NaOH solution to H2O2 solution was 10:2, the amount of biochar added was 0.02 g / L, the pH value of the golden transparent liquid was adjusted to 7 with HCl, and then the liquid was dialyzed for 24 h, wherein deionized water was replaced every 6 h, the volume ratio of the initially added golden transparent liquid to deionized water was 1:100, the dialysis bag was MW3500, and CDs were obtained after removing the salt.

[0075] (7) The CDs obtained in step (6) is dissolved in deionized water at a dosage of 0.05 mg / ml, and the pH value of the CDs solution is adjusted to 9 with aqueous ammonia. The Mo-La-TiO2 nanotube array titanium sheet obtained in step (5) is used as the cathode and the graphite sheet is used as the anode. Electrophoresis is performed in the CDs solution at a voltage of 6 V for 6 min. After the electrophoresis, the CDs-composite Mo-La-TiO2 nanotubes are ultrasonically cleaned for 30 s and dried in an electric blower drying oven to obtain CDs-composite Mo-La-TiO2 nanotubes.

[0076] Example 6

[0077] A thin film structure of CDs composite Mo-La ion co-doped TiO2 nanotubes, the specific preparation steps are as follows:

[0078] (1) A 0.2 mm × 20 mm × 30 mm high-purity titanium sheet was used as the substrate and polished with 200#, 400#, 800#, 1000#, 1500#, 2000#, and 2500# sandpapers in sequence until there were no obvious scratches on the surface; then, ultrasonic cleaning was performed with acetone, anhydrous ethanol, and deionized water for 10 min in sequence and dried for later use.

[0079] (2) Dissolve ammonium fluoride in deionized water in a beaker, and then add ethylene glycol with a concentration of 95% to prepare an ammonium fluoride electrolyte, wherein the volume ratio of deionized water to ethylene glycol is 95:5, and the amount of ammonium fluoride added is 1 mol / L. Stir it evenly on a magnetic stirrer. The titanium sheet treated in (1) is used as the anode and the graphite sheet is used as the cathode. Connect a DC constant voltage power supply to the obtained electrolyte, adjust the voltage to 30 V, and determine the oxidation time to be 1 hour. After the oxidation is completed, the prepared TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute, and then dried for use.

[0080] (3) Sodium molybdate is used as a Mo ion source, and sodium molybdate is dissolved in deionized water to obtain a sodium molybdate aqueous solution as an electrolyte, wherein the amount of sodium molybdate added is 0.01 mol / L. The titanium sheet with TiO2 nanotubes attached obtained in step (2) is used as a cathode, and the graphite sheet is used as an anode. A DC power supply is applied, and the voltage is adjusted to 6 V. The oxidation time is 1 hour. After the end, the TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute, and then dried for use.

[0081] (4) Lanthanum nitrate is used as a La ion source, and lanthanum nitrate is dissolved in deionized water to obtain a lanthanum nitrate aqueous solution as an electrolyte, wherein the amount of lanthanum nitrate added is 0.005 mol / L, and the Mo-doped TiO2 nanotubes dried and set aside in step (3) are placed at the cathode, and graphite is placed at the anode, and an electrochemical reaction is performed to dope La ions, and the voltage is adjusted to 6 V and the oxidation time is 1 hour. After the end, the Mo and La co-doped TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute and dried for later use.

[0082] (5) The Mo and La co-doped TiO2 nanotubes obtained in step (4) are placed in a muffle furnace for calcination, the heating rate is controlled to be 5°C / min, the calcination temperature is 450°C, the calcination time is 3h, and the Mo and La ion co-doped TiO2 nanotube arrays are obtained after cooling in the furnace.

[0083] (6) Dispersing glucose in deionized water, wherein the amount of glucose added is 0.1 g / ml, adding the obtained glucose aqueous solution into a reactor, controlling the heating rate of the reactor to 5°C / min, performing a hydrolysis reaction at 180°C, and obtaining a hydrolysis mixture for 6 hours; placing the mixture in a centrifuge and centrifuging it at 7000 r / min for 7 minutes to separate the suspension and the hydrochar, washing the hydrochar with deionized water and ethanol for 3 times respectively, and then drying it in an oven to obtain biochar; dispersing the biochar in 0.4 mol / L NaOH solution was added with H2O2 solution and stirred at room temperature for 8 h to obtain a golden transparent liquid, wherein the volume ratio of 0.4 mol / L NaOH solution to H2O2 solution was 10:2, the amount of biochar added was 0.02 g / L, the pH value of the golden transparent liquid was adjusted to 7 with HCl, and then the liquid was dialyzed for 24 h, wherein deionized water was replaced every 6 h, the volume ratio of the initially added golden transparent liquid to deionized water was 1:100, the dialysis bag was MW3500, and CDs were obtained after removing the salt.

[0084] (7) The CDs obtained in step (6) is dissolved in deionized water at a dosage of 0.05 mg / ml, and the pH value of the CDs solution is adjusted to 9 with aqueous ammonia. The Mo-La-TiO2 nanotube array titanium sheet obtained in step (5) is used as the cathode and the graphite sheet is used as the anode. Electrophoresis is performed in the CDs solution at a voltage of 6 V for 6 min. After the electrophoresis, the CDs-composite Mo-La-TiO2 nanotubes are ultrasonically cleaned for 30 s and dried in an electric blower drying oven to obtain CDs-composite Mo-La-TiO2 nanotubes.

[0085] Example 7

[0086] A thin film structure of CDs composite Mo-La ion co-doped TiO2 nanotubes, the specific preparation steps are as follows:

[0087] (1) A 0.2 mm × 20 mm × 30 mm high-purity titanium sheet was used as the substrate and polished with 200#, 400#, 800#, 1000#, 1500#, 2000#, and 2500# sandpapers in sequence until there were no obvious scratches on the surface; then, ultrasonic cleaning was performed with acetone, anhydrous ethanol, and deionized water for 10 min in sequence and dried for later use.

[0088] (2) Dissolve ammonium fluoride in deionized water in a beaker, and then add ethylene glycol with a concentration of 95% to prepare an ammonium fluoride electrolyte, wherein the volume ratio of deionized water to ethylene glycol is 95:5, and the amount of ammonium fluoride added is 1 mol / L. Stir it evenly on a magnetic stirrer. The titanium sheet treated in (1) is used as the anode and the graphite sheet is used as the cathode. Connect a DC constant voltage power supply to the obtained electrolyte, adjust the voltage to 10 V, and determine the oxidation time to be 1 hour. After the oxidation is completed, the prepared TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute, and then dried for use.

[0089] (3) Sodium molybdate is used as a Mo ion source, and sodium molybdate is dissolved in deionized water to obtain a sodium molybdate aqueous solution as an electrolyte, wherein the amount of sodium molybdate added is 0.01 mol / L. The titanium sheet with TiO2 nanotubes attached obtained in step (2) is used as a cathode, and the graphite sheet is used as an anode. A DC power supply is applied, and the voltage is adjusted to 6 V. The oxidation time is 1 hour. After the end, the TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute, and then dried for use.

[0090] (4) Lanthanum nitrate is used as a La ion source, and lanthanum nitrate is dissolved in deionized water to obtain a lanthanum nitrate aqueous solution as an electrolyte, wherein the amount of lanthanum nitrate added is 0.005 mol / L, and the Mo-doped TiO2 nanotubes dried and set aside in step (3) are placed at the cathode, and graphite is placed at the anode, and an electrochemical reaction is performed to dope La ions, and the voltage is adjusted to 6 V and the oxidation time is 1 hour. After the end, the Mo and La co-doped TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute and dried for later use.

[0091] (5) The Mo and La co-doped TiO2 nanotubes obtained in step (4) are placed in a muffle furnace for calcination, the heating rate is controlled to be 5°C / min, the calcination temperature is 450°C, the calcination time is 3h, and the Mo and La ion co-doped TiO2 nanotube arrays are obtained after cooling in the furnace.

[0092] (6) Dispersing glucose in deionized water, wherein the amount of glucose added is 0.1 g / ml, adding the obtained glucose aqueous solution into a reactor, controlling the heating rate of the reactor to 5°C / min, performing a hydrolysis reaction at 180°C, and obtaining a hydrolysis mixture for 6 hours; placing the mixture in a centrifuge and centrifuging it at 7000 r / min for 7 minutes to separate the suspension and the hydrochar, washing the hydrochar with deionized water and ethanol for 3 times respectively, and then drying it in an oven to obtain biochar; dispersing the biochar in 0.4 mol / L NaOH solution was added with H2O2 solution and stirred at room temperature for 8 h to obtain a golden transparent liquid, wherein the volume ratio of 0.4 mol / L NaOH solution to H2O2 solution was 10:2, the amount of biochar added was 0.02 g / L, the pH value of the golden transparent liquid was adjusted to 7 with HCl, and then the liquid was dialyzed for 24 h, wherein deionized water was replaced every 6 h, the volume ratio of the initially added golden transparent liquid to deionized water was 1:100, the dialysis bag was MW3500, and CDs were obtained after removing the salt.

[0093] (7) The CDs obtained in step (6) is dissolved in deionized water at a dosage of 0.05 mg / ml, and the pH value of the CDs solution is adjusted to 9 with aqueous ammonia. The Mo-La-TiO2 nanotube array titanium sheet obtained in step (5) is used as the cathode and the graphite sheet is used as the anode. Electrophoresis is performed in the CDs solution at a voltage of 6 V for 6 min. After the electrophoresis, the CDs-composite Mo-La-TiO2 nanotubes are ultrasonically cleaned for 30 s and dried in an electric blower drying oven to obtain CDs-composite Mo-La-TiO2 nanotubes.

[0094] Example 8

[0095] A thin film structure of CDs composite Mo-La ion co-doped TiO2 nanotubes, the specific preparation steps are as follows:

[0096] (1) A 0.2 mm × 20 mm × 30 mm high-purity titanium sheet was used as the substrate and polished with 200#, 400#, 800#, 1000#, 1500#, 2000#, and 2500# sandpapers in sequence until there were no obvious scratches on the surface; then, ultrasonic cleaning was performed with acetone, anhydrous ethanol, and deionized water for 10 min in sequence and dried for later use.

[0097] (2) Dissolve ammonium fluoride in deionized water in a beaker, and then add ethylene glycol with a concentration of 95% to prepare an ammonium fluoride electrolyte, wherein the volume ratio of deionized water to ethylene glycol is 95:5, and the amount of ammonium fluoride added is 0.1 mol / L. Stir it evenly on a magnetic stirrer. The titanium sheet treated in (1) is used as the anode and the graphite sheet is used as the cathode. Connect a DC constant voltage power supply to the obtained electrolyte, adjust the voltage to 40 V, and determine the oxidation time to be 1 hour. After the oxidation is completed, the prepared TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute, and then dried for use.

[0098] (3) Sodium molybdate is used as a Mo ion source, and sodium molybdate is dissolved in deionized water to obtain a sodium molybdate aqueous solution as an electrolyte, wherein the amount of sodium molybdate added is 0.01 mol / L. The titanium sheet with TiO2 nanotubes attached obtained in step (2) is used as a cathode, and the graphite sheet is used as an anode. A DC power supply is applied, and the voltage is adjusted to 6 V. The oxidation time is 1 hour. After the end, the TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute, and then dried for use.

[0099] (4) Lanthanum nitrate is used as a La ion source, and lanthanum nitrate is dissolved in deionized water to obtain a lanthanum nitrate aqueous solution as an electrolyte, wherein the amount of lanthanum nitrate added is 0.005 mol / L, and the Mo-doped TiO2 nanotubes dried and set aside in step (3) are placed at the cathode, and graphite is placed at the anode, and an electrochemical reaction is performed to dope La ions, and the voltage is adjusted to 6 V and the oxidation time is 1 hour. After the end, the Mo and La co-doped TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute and dried for later use.

[0100] (5) The Mo and La co-doped TiO2 nanotubes obtained in step (4) are placed in a muffle furnace for calcination, the heating rate is controlled to be 5°C / min, the calcination temperature is 450°C, the calcination time is 3h, and the Mo and La ion co-doped TiO2 nanotube arrays are obtained after cooling in the furnace.

[0101] (6) Dispersing glucose in deionized water, wherein the amount of glucose added is 0.1 g / ml, adding the obtained glucose aqueous solution into a reactor, controlling the heating rate of the reactor to 5°C / min, performing a hydrolysis reaction at 180°C, and obtaining a hydrolysis mixture for 6 hours; placing the mixture in a centrifuge and centrifuging it at 7000 r / min for 7 minutes to separate the suspension and the hydrochar, washing the hydrochar with deionized water and ethanol for 3 times respectively, and then drying it in an oven to obtain biochar; dispersing the biochar in 0.4 mol / L NaOH solution was added with H2O2 solution and stirred at room temperature for 8 h to obtain a golden transparent liquid, wherein the volume ratio of 0.4 mol / L NaOH solution to H2O2 solution was 10:2, the amount of biochar added was 0.02 g / L, the pH value of the golden transparent liquid was adjusted to 7 with HCl, and then the liquid was dialyzed for 24 h, wherein deionized water was replaced every 6 h, the volume ratio of the initially added golden transparent liquid to deionized water was 1:100, the dialysis bag was MW3500, and CDs were obtained after removing the salt.

[0102] (7) The CDs obtained in step (6) is dissolved in deionized water at a dosage of 0.05 mg / ml, and the pH value of the CDs solution is adjusted to 9 with aqueous ammonia. The Mo-La-TiO2 nanotube array titanium sheet obtained in step (5) is used as the cathode and the graphite sheet is used as the anode. Electrophoresis is performed in the CDs solution at a voltage of 6 V for 6 min. After the electrophoresis, the CDs-composite Mo-La-TiO2 nanotubes are ultrasonically cleaned for 30 s and dried in an electric blower drying oven to obtain CDs-composite Mo-La-TiO2 nanotubes.

[0103] Comparative Example 1

[0104] As a control, the difference from Example 1 is that no compounding with CDs is performed. The specific preparation steps are as follows:

[0105] (1) A 0.2 mm × 20 mm × 30 mm high-purity titanium sheet was used as the substrate and polished with 200#, 400#, 800#, 1000#, 1500#, 2000#, and 2500# sandpapers in sequence until there were no obvious scratches on the surface; then, ultrasonic cleaning was performed with acetone, anhydrous ethanol, and deionized water for 10 min in sequence and dried for later use.

[0106] (2) Dissolve ammonium fluoride in deionized water in a beaker, and then add ethylene glycol with a concentration of 95% to prepare an ammonium fluoride electrolyte, wherein the volume ratio of deionized water to ethylene glycol is 95:5, and the amount of ammonium fluoride added is 0.25 mol / L. Stir it evenly on a magnetic stirrer. The titanium sheet treated in (1) is used as the anode and the graphite sheet is used as the cathode. Connect a DC constant voltage power supply to the obtained electrolyte, adjust the voltage to 30 V, and determine the oxidation time to be 1 hour. After the oxidation is completed, the prepared TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute, and then dried for use.

[0107] (3) Sodium molybdate is used as a Mo ion source, and sodium molybdate is dissolved in deionized water to obtain a sodium molybdate aqueous solution as an electrolyte, wherein the amount of sodium molybdate added is 0.01 mol / L. The titanium sheet with TiO2 nanotubes attached obtained in step (2) is used as a cathode, and the graphite sheet is used as an anode. A DC power supply is applied, and the voltage is adjusted to 6 V. The oxidation time is 1 hour. After the end, the TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute, and then dried for use.

[0108] (4) Lanthanum nitrate is used as a La ion source, and lanthanum nitrate is dissolved in deionized water to obtain a lanthanum nitrate aqueous solution as an electrolyte, wherein the amount of lanthanum nitrate added is 0.005 mol / L, and the Mo-doped TiO2 nanotubes dried and set aside in step (3) are placed at the cathode, and graphite is placed at the anode, and an electrochemical reaction is performed to dope La ions, and the voltage is adjusted to 6 V and the oxidation time is 1 hour. After the end, the Mo and La co-doped TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute and dried for later use.

[0109] (5) The Mo and La co-doped TiO2 nanotubes obtained in step (4) are placed in a muffle furnace for calcination, the heating rate is controlled to be 5°C / min, the calcination temperature is 450°C, the calcination time is 3h, and the Mo and La ion co-doped TiO2 nanotube arrays are obtained after cooling in the furnace.

[0110] Comparative Example 2

[0111] As a control, the difference from Example 1 is that Mo ions and La ions are not doped. The specific preparation steps are as follows:

[0112] (1) A 0.2 mm × 20 mm × 30 mm high-purity titanium sheet was used as the substrate and polished with 200#, 400#, 800#, 1000#, 1500#, 2000#, and 2500# sandpapers in sequence until there were no obvious scratches on the surface; then, ultrasonic cleaning was performed with acetone, anhydrous ethanol, and deionized water for 10 min in sequence and dried for later use.

[0113] (2) Dissolve ammonium fluoride in deionized water in a beaker, and then add ethylene glycol with a concentration of 95% to prepare an ammonium fluoride electrolyte, wherein the volume ratio of deionized water to ethylene glycol is 95:5, and the amount of ammonium fluoride added is 0.25 mol / L. Stir it evenly on a magnetic stirrer. The titanium sheet treated in (1) is used as the anode and the graphite sheet is used as the cathode. Connect a DC constant voltage power supply to the obtained electrolyte, adjust the voltage to 30 V, and determine the oxidation time to be 1 hour. After the oxidation is completed, the prepared TiO2 nanotubes are ultrasonically cleaned with deionized water for 1 minute, and then dried for use.

[0114] (3) Dispersing glucose in deionized water, wherein the amount of glucose added is 0.1 g / ml, adding the obtained glucose aqueous solution into a reactor, controlling the heating rate of the reactor to 5°C / min, performing a hydrolysis reaction at 180°C, and obtaining a hydrolysis mixture for 6 hours; placing the mixture in a centrifuge and centrifuging it at 7000 r / min for 7 minutes to separate the suspension and the hydrochar, washing the hydrochar with deionized water and ethanol for 3 times respectively, and then drying it in an oven to obtain biochar; dispersing the biochar in 0.4 mol / L NaOH solution was added with H2O2 solution and stirred at room temperature for 8 h to obtain a golden transparent liquid, wherein the volume ratio of 0.4 mol / L NaOH solution to H2O2 solution was 10:3, the amount of biochar added was 0.02 g / L, the pH value of the golden transparent liquid was adjusted to 7 with HCl, and then the liquid was dialyzed for 24 h, wherein deionized water was replaced every 6 h, the volume ratio of the initially added golden transparent liquid to deionized water was 1:100, the dialysis bag was MW3500, and CDs were obtained after removing the salt.

[0115] (4) The CDs obtained in step (3) is dissolved in deionized water at a dosage of 0.05 mg / ml. The pH value of the CDs solution is adjusted to 9 with aqueous ammonia. The titanium sheet of the TiO2 nanotube array obtained in step (2) is used as the cathode and the graphite sheet is used as the anode. Electrophoresis is performed in the CDs solution at a voltage of 6 V for 6 min. After the electrophoresis, the CDs-composite Mo-La-TiO2 nanotubes are ultrasonically cleaned for 30 s and dried in an electric blower drying oven to obtain CDs-composite TiO2 nanotubes.

[0116] Figure 1 This is a morphology diagram of the CDs prepared in Example 1 of the present invention. It can be seen from the figure that the CDs are spherical and have a size of less than 50 nm.

[0117] Figure 2This is a scanning electron microscope image of the CDs composite Mo-La ion co-doped TiO2 nanotubes of Examples 1 to 4 of the present invention. It can be seen from the image that the CDs composite Mo-La ion co-doped TiO2 nanotube array is arranged in an orderly manner, the surface is smooth and flat, the tube mouths are all round, and the tube diameter is 70nm to 90nm.

[0118] Figure 3 The scanning electron microscope images of the cross-sections of TiO2 nanotubes obtained in Examples 1 to 4 of the present invention show that the length of the CDs composite Mo-La ion co-doped TiO2 nanotubes is 1.5um to 3um. Compared with Example 1, the length of the nanotubes in Example 2 is significantly increased, indicating that increasing the anodization time in the preparation stage of TiO2 nanotubes can promote the growth of nanotubes.

[0119] Figure 4 Table 1 shows the UV-Vis test results of the TiO2 nanotubes of Examples 1 to 4 and Comparative Examples 1 to 2. Table 1 shows the light absorption band edge and bandgap width of the TiO2 nanotubes calculated by the tangent method. Figure 2 It can be seen from Table 1 that the light absorption of the TiO2 nanotubes after Mo-La ion doping and CDs composite modification has undergone a significant red shift, the light absorption band edge has increased significantly, the band gap has decreased significantly, and the light absorption range has been widened. Compared with the Mo-La ion co-doped TiO2 nanotubes in Comparative Example 1 and the CDs composite TiO2 nanotubes in Comparative Example 2, the light absorption band edge of the CDs composite Mo-La ion co-doped TiO2 nanotubes in Examples 1 to 4 of the present invention has increased more, and the band gap has decreased more significantly. Among them, the modification effect of the TiO2 nanotubes in Example 1 is the most obvious, the light absorption band edge has been widened to 441nm, and the band gap has been reduced to 2.81eV, indicating that the present invention has achieved a significant improvement in the light absorption band edge of the TiO2 nanotubes through the CDs composite and Mo composite. 6+ ,La 3+ The synergistic effect of co-doping effectively improves the photocatalytic activity of TiO2.

[0120] Table 1 Optical absorption band edge and bandgap width of TiO2 nanotubes obtained in Examples 1 to 4 and Comparative Examples 1 to 2

[0121] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Light absorption band edge 441nm 424nm 417nm 435nm 406nm 402nm Bandgap 2.81eV 2.92eV 2.97eV 2.85eV 3.05eV 3.08eV

[0122] Figure 5The scanning electron microscope images of the TiO2 nanotubes obtained in Examples 5 to 8 show that the diameter of the TiO2 nanotubes decreases with increasing ammonium fluoride concentration, but increases with increasing oxidation voltage. Compared with Example 1, Example 5 reduces the diameter of the TiO2 nanotubes to about 75 nm by reducing the oxidation voltage, Example 6 reduces the diameter of the TiO2 nanotubes to about 50 nm by increasing the ammonium fluoride concentration, and Example 7 reduces the diameter of the nanotubes to about 30 nm by simultaneously increasing the ammonium fluoride concentration and reducing the oxidation voltage; Example 8 increases the diameter of the TiO2 nanotubes to about 90 nm by simultaneously reducing the ammonium fluoride concentration and increasing the oxidation voltage. In addition to the change in diameter, the order and surface smoothness of the TiO2 nanotubes also change with the concentration of ammonium fluoride and the oxidation voltage. Therefore, the diameter, length, surface smoothness and order of the TiO2 nanotubes can be adjusted by adjusting the concentration of ammonium fluoride, the anodic oxidation voltage and the reaction time.

Claims

1. A method for preparing a CDs composite Mo-La ion co-doped TiO2 nanotube array, characterized in that: TiO2 nanotube arrays were obtained by co-doping CDs with Mo-La ions. The specific preparation steps are as follows: (1) Use pure titanium sheet as the substrate, polish until there are no obvious scratches on the surface, clean it, dry it and set it aside; (2) dissolving ammonium fluoride in deionized water, adding ethylene glycol, and stirring evenly to obtain an ammonium fluoride-ethylene glycol-water solution as an electrolyte solution, using the titanium sheet treated in step (1) as an anode and the graphite sheet as a cathode, connecting a DC constant voltage power supply to the obtained electrolyte solution, controlling the oxidation voltage and time to perform anodization, and obtaining a titanium sheet with TiO2 nanotubes attached after the completion of the anodic oxidation, washing, drying, and setting aside; (3) Dissolving a soluble Mo inorganic salt in deionized water to prepare an electrolyte solution containing Mo ions, using the titanium sheet with attached TiO2 nanotubes obtained in step (2) as a cathode and the graphite sheet as an anode, applying a DC power supply, controlling the reaction voltage and reaction time, and conducting Mo 6+ After the doping reaction is completed, a titanium sheet doped with Mo ions and TiO2 nanotubes is obtained, which is cleaned, dried and set aside; (4) dissolving a soluble La inorganic salt in deionized water to prepare an electrolyte solution containing La ions, using the titanium sheet doped with Mo ions obtained in step (3) as a cathode and a graphite sheet as an anode, applying a DC power supply, and controlling the reaction voltage and reaction time to carry out La 3+ Doping reaction, after the reaction is completed, a titanium sheet of Mo-La co-doped TiO2 nanotubes is obtained, which is cleaned, dried and set aside; (5) placing the Mo-La co-doped TiO2 nanotube titanium sheet obtained in step (4) into a muffle furnace for calcination to obtain a Mo-La-TiO2 nanotube array titanium sheet; (6) Glucose is dispersed in deionized water to form a glucose aqueous solution, the amount of glucose added to the deionized water is 0.067~0.2g / mL, and added to a reactor for hydrothermal reaction. The conditions of the hydrothermal reaction are: a heating rate of 4℃ / min~10℃ / min, and a reaction at 150℃~250℃ for 5~8h to obtain a hydrothermal mixture, and the mixture is centrifuged in a centrifuge to separate the suspension and the hydrochar, and the hydrochar is washed and then dried in an oven to obtain biochar, and the biochar is dispersed in NaOH In the solution, H2O2 solution is added and stirred, the volume ratio of NaOH solution to H2O2 solution is 10:1~10:3, wherein the concentration of NaOH solution used is 0.05mol / L~1mol / L, and the concentration of H2O2 solution is 7.5%; the amount of biochar added to the mixed solution of NaOH solution and H2O2 solution is 0.01g / L~0.02g / L, and a golden transparent liquid is obtained, the pH value of the golden transparent liquid is adjusted, and then the liquid is dialyzed to obtain carbon dots CDs; (7) The CDs obtained in step (6) is dissolved in deionized water to prepare a CDs solution, the pH value of the CDs solution is adjusted, and the Mo-La-TiO2 nanotube array titanium sheet obtained in step (5) is used as a cathode and the graphite sheet is used as an anode. Electrophoresis is performed in the CDs solution to obtain a CDs composite Mo-La-TiO2 nanotube array, which is then ultrasonically cleaned and dried.

2. The method for preparing the CDs composite Mo-La ion co-doped TiO2 nanotube array according to claim 1, characterized in that: In step (1), the pure titanium sheet is polished with 200#, 400#, 800#, 1000#, 1500#, 2000#, and 2500# sandpaper in sequence until there are no obvious scratches on the surface; and ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water in sequence.

3. The method for preparing the CDs composite Mo-La ion co-doped TiO2 nanotube array according to claim 1, characterized in that: In step (2), the volume ratio of deionized water to ethylene glycol is 95:5-80:20; the amount of ammonium fluoride added to the deionized water is 0.1 mol / L-1 mol / L; the oxidation voltage is 10 V-40 V, and the oxidation time is 0.5 h-3 h.

4. The method for preparing the CDs composite Mo-La ion co-doped TiO2 nanotube array according to claim 1, characterized in that: The inorganic salt of Mo in step (3) includes any one of analytically pure sodium molybdate, ammonium molybdate, and magnesium molybdate. The amount of the inorganic salt of Mo added to deionized water is 0.01 mol / L~0.1 mol / L, the reaction voltage is 4V~10V, and the reaction time is 0.5h~2h.

5. The method for preparing the CDs composite Mo-La ion co-doped TiO2 nanotube array according to claim 1, characterized in that: The inorganic salt of La in step (4) includes any one of analytically pure lanthanum nitrate, lanthanum chloride, and lanthanum sulfate. The amount of the inorganic salt of La added in deionized water is 0.005 mol / L~0.05 mol / L, the reaction voltage is 4V~10V, and the reaction time is 0.5h~2h.

6. The method for preparing the CDs composite Mo-La ion co-doped TiO2 nanotube array according to claim 1, characterized in that: The molar ratio of Mo ions and La ions doped in step (3) and step (4) is 2:

1.

7. The method for preparing the CDs composite Mo-La ion co-doped TiO2 nanotube array according to claim 1, characterized in that: The calcination conditions in step (5) are: calcination temperature is 450°C to 550°C, heating rate is 4°C / min to 10°C / min, and calcination time is 2h to 4h.

8. The method for preparing the CDs composite Mo-La ion co-doped TiO2 nanotube array according to claim 1, characterized in that: In step (6), the centrifugal speed is 7000 r / min-10000 r / min for 5-10 min; the hydrochar is washed three times with deionized water and ethanol respectively.

9. The method for preparing the CDs composite Mo-La ion co-doped TiO2 nanotube array according to claim 1, characterized in that: In step (6), the pH value of the golden yellow transparent liquid is adjusted to 5-7 with HCl, and then the golden yellow transparent liquid is dialyzed for 24h~36h, and deionized water is replaced every 5~8h, wherein the volume ratio of the initially added golden yellow transparent liquid to deionized water is 1: (70~100), and the dialysis bag is MW3500.

10. The method for preparing the CDs composite Mo-La ion co-doped TiO2 nanotube array according to claim 1, characterized in that: Step (7) The amount of CDs added to deionized water is 0.01-0.5 mg / mL, and the pH value of the CDs solution is adjusted to 8-10 with ammonia water; the electrophoresis voltage is 4V-10V, and the electrophoresis time is 4min-15min.